2021
DOI: 10.1038/s41598-021-96740-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of transcriptomic profiling to identify candidate genes involved in Polyporus umbellatus sclerotial formation affected by oxalic acid

Abstract: Polyporus umbellatus is a precious medicinal fungus. Oxalic acid was observed to affect sclerotial formation and sclerotia possessed more medicinal compounds than mycelia. In this study, the transcriptome of P. umbellatus was analysed after the fungus was exposed to various concentrations of oxalic acid. The differentially expressed genes (DEGs) encoding a series of oxidases were upregulated, and reductases were downregulated, in the low-oxalic-acid (Low OA) group compared to the control (No OA) group, while t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Many studies in fungi have profiled transcriptional changes in fungal mycelia in response to oxalic acid [ 13 ]. Consistent with our observations, excessive oxalic acid down-regulated the expression level of many genes [ 14 ]. The wood-degradation enzyme system of white and brown rot fungi is crucial for the mycelial growth performance and biological efficiency [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many studies in fungi have profiled transcriptional changes in fungal mycelia in response to oxalic acid [ 13 ]. Consistent with our observations, excessive oxalic acid down-regulated the expression level of many genes [ 14 ]. The wood-degradation enzyme system of white and brown rot fungi is crucial for the mycelial growth performance and biological efficiency [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Transcriptome-based analysis of a wood-rot fungus Abortiporus biennis revealed that the addition of oxalic acid significantly promoted the expression of cellulolytic enzyme genes, but significantly inhibited the expression of lignolytic enzyme genes [ 13 ]. Xing et al used transcriptomic profiling to identify candidate genes involved in sclerotial formation by Polyporus umbellatus in the presence of oxalic acid [ 14 ]. These transcriptome data indicated that RNA-seq is a rapid and high-throughput approach for obtaining comprehensive differentially expressed genes (DEGs) of oxalic-acid-treated edible fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory role of CRZ1 in ganoderic acid biosynthesis has only been investigated in Ganoderma lucidum ( Li and Zhong, 2020 ). Previous studies have reported that environmental factors (oxidation, temperature, medium) affect the formation of P. umbellatus sclerotia ( Xing et al, 2013 , 2015 , 2021 ; Bandara et al, 2015 ). Here, we further investigated the function of the transcription factor CRZ1 in P. umbellatus and whether it is associated with resistance and sclerotia formation like other fungi.…”
Section: Introductionmentioning
confidence: 99%